Effect of Traditional Chinese Medicine hot compress and acupoint application on prevention of abdominal distension and constipation after multiple-level spinal fixation surgery (中药封包和穴位贴敷预防多节段脊柱手术患者腹胀便秘的效果观察) - HUANG Lijun (黄丽君); CHEN Zihao (陈子豪); OU Zhaolan (欧肇兰); LUO Chunxiao (罗春晓) (中西医结合护理)
Objective To compare the effect of Traditional Chinese Medicine (TCM) hot compress and acupoint application on prevention of abdominal distension and constipation after multiple-level spinal fixation surgery. Methods This study was a prospective, randomized controlled clinical trial conducted at a single institution. From August 2020 to November 2021, patients who met the inclusion criteria were allocated to TCM hot compress group and acupoint application group (each for 30 patients). Another 30 more patients without intervention were recruited as control group. Primary outcomes included the time to first flatus and time to first defecation. Secondary outcomes included 3-day postoperative abdominal girth, 3-day postoperative abdominal distension and patient¡¯s satisfaction. Results Time to first flatus was (20. 80+-13. 00) h in TCM hot compress group, (21. 70+-13. 70)h in acupoint application group, both of which was lower than (38. 00+-14. 60)h of control group (P£¼0. 01; P£¼0. 01). Time to first defecation was (69. 10+-24. 90)h in TCM hot compress group, lower than(82. 80+-26. 50)h in acupoint application group (P£¼0. 05), both of which was lower than(100. 80+-28. 20)h in control group(P£¼0. 01; P£¼0. 05). The 3-day postoperative bloating score was(0. 23+-0. 43)in TCM hot compress group, lower than (0. 5+-0. 73) in acupoint application group (P£¼0. 05), both of them lower than (1. 07+-0. 87) in control group (P£¼0. 01; P£¼0. 01). The satisfaction rate was 100%(30/30) in Chinese medicine hot compress group, higher than 90. 00%(27/30) in acupoint application group and73. 33%(22/30) in control group (P£¼0. 01; P£¼0. 01). Conclusion Both TCM hot compress and acupoint application are effective in preventing abdominal distension and constipation after multiple-level spinal fixation surgery. TCM hot compress therapy shows a better therapeutic effect in aspects of shorter time to first defecation and relief of abdominal distension. (目的 比较中药封包与穴位贴敷预防多节段脊柱手术患者术后腹胀、便秘发生的效果。方法 本研究为前瞻性随机对照研究。选取2020年8月—2021年11月医院收治的符合纳入标准的患者60例, 随机分为中药封包组和穴位贴敷组, 每组30例, 在常规术后护理的基础上分别实施中药封包和穴位贴敷疗法。收集同期未入组的30例患者作为对照组。主要指标为术后首次排气、排便时间, 次要指标为术后第3天腹围、术后第3天腹胀评分及患者满意度。结果 首次排气时间中药封包组为(20. 80±13. 00)h, 穴位贴敷组为(21. 70+-13. 70)h, 均低于对照组的(38. 00+-14. 60)h(P＜0. 01; P＜0. 01)。首次排便时间中药封包组为(69. 10+_24. 90)h, 穴位贴敷组为(82. 80+-26. 50)h, 均低于对照组的(100. 80+-28. 20)h(P＜0. 01; P＜0. 05), 且中药封包组优于穴位贴敷组(P＜0. 05)。术后3 d腹胀评分, 中药封包组为(0. 23+-0. 43)分, 穴位贴敷组为(0. 57+->0. 73)分, 均低于对照组的(1. 07+->0. 87)分(P＜0. 01; P＜0. 01), 且中药封包组优于穴位贴敷组(P＜0. 05)。中药封包组满意率100%(30/30), 高于穴位贴敷的90. 00%(27/30)及对照组的73. 33%(22/30)(P＜0. 01; P＜0. 01)。结论 中药封包及穴位贴敷均能有效预防多节段脊柱手术患者术后腹胀和便秘, 且中药封包治疗在缩短患者首次排便时间、缓解腹胀症状等方面均优于穴位贴敷治疗。)